2009
DOI: 10.1093/sleep/32.12.1593
|View full text |Cite
|
Sign up to set email alerts
|

Eszopiclone Prevents Excitotoxicity and Neurodegeneration in the Hippocampus Induced by Experimental Apnea

Abstract: Eszopiclone was determined to suppress the apnea-induced hyperexcitability of hippocampal CA1 neurons, thereby reducing/eliminating neurotoxicity. These data lend credence to our hypothesis that eszopiclone, exclusive of its hypnotic actions, has the capacity to function as a potent neuroprotective agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…This hypothesis is supported by the pivotal role played by the amygdala in emotional and cerebral circuits (LeDoux,2000) and related to pathological conditions, such as depression, wherein amygdaloid dysfunction together with disturbances of AS has been shown to occur (Maquet and Franck,1997). Recently, we demonstrated that recurrent apnea in guinea pigs (which models obstructive sleep apnea syndrome in humans; Fung et al,2007,2009) produces neurodegeneration/apoptosis in CNA neurons (Zhang et al,2009). This finding suggests that dysfunction of the excitatory CNA pathway to the NPO may contribute to AS disturbances as well as to the generation of comorbidities that occur due to pathologies that involve the amygdala and others that also occur in conjunction with obstructive sleep apnea.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by the pivotal role played by the amygdala in emotional and cerebral circuits (LeDoux,2000) and related to pathological conditions, such as depression, wherein amygdaloid dysfunction together with disturbances of AS has been shown to occur (Maquet and Franck,1997). Recently, we demonstrated that recurrent apnea in guinea pigs (which models obstructive sleep apnea syndrome in humans; Fung et al,2007,2009) produces neurodegeneration/apoptosis in CNA neurons (Zhang et al,2009). This finding suggests that dysfunction of the excitatory CNA pathway to the NPO may contribute to AS disturbances as well as to the generation of comorbidities that occur due to pathologies that involve the amygdala and others that also occur in conjunction with obstructive sleep apnea.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs enhancing GABA-A signaling may thus represent potential strategies to treat or prevent the progressive motorneuron degeneration in ALS patients (Supplementary Table 7). In this regard, some GABA-A agonists (ganaxolone, clomethiazole, GT 1061, clorazepate, zolpidem, eszopiclone, pentobarbital, GT 1061) have shown to prevent excitotoxicity and neuronal loss, exerting neuroprotective effects in several neurological disorders, such as Alzheimer's and Parkinson's [88][89][90][91].…”
Section: Review Morello and Cavallaromentioning
confidence: 99%
“…This finding is especially significant because almost every known neuroprotective substance acts by suppressing or inhibiting neural activity. Consequently, even though hypocretin is an excitatory neuropeptide, in this case its effects are more closely related to those produced by inhibitory neurotransmitters (54,189).…”
Section: Control Of Survival-related Processes By the Hypocretinergicmentioning
confidence: 99%